Corruption and money laundering in a global context (Legal journal - Research in Legal and Social Sciences, 2021)
This investigation addresses the cases of punishable acts related to money laundering and others that are directly or indirectly related to acts of corruption. These in turn, by a legal procedure can lead to cases of asset recovery of the property of the investigated subject, depending on the origin or place where they are, for their recovery in favor of the State. In this understanding, SENABICO is in charge of the administration of seized or forfeited assets, in the context of an investigation. At the macro level, among the decisive factors for the investigations, mention is made of corruption linked to the Odebrecht case, which involves countries such as: Peru, Brazil, Colombia and Ecuador. Europe was not isolated from this practice, which was evidenced by the resignation of the President of the Kingdom of Spain and the abdication of the King; on the other hand, the case of CONMEBOLL, and how not to highlight The Panama Papers. These episodes, without a doubt, were roughly some of the immediate factors that made society wake up. Transparency and access to information marked part of the route to ensure that justice has the tools to act, investigate, at the same time exercise control and support management. In all these cases, the role of the press and new technologies acted as an ally to reach society, with information or disinformation, until the indignation of a society tired of privileges was achieved. Paraguay made significant progress by ordering the first investigations involving people from civil society and public administration authorities.
Keywords: corruption; money laundering; factors; asset recovery; transparency